2008
DOI: 10.1186/1471-2458-8-37
|View full text |Cite
|
Sign up to set email alerts
|

A hidden HIV epidemic among women in Vietnam

Abstract: BackgroundThe HIV epidemic in Vietnam is still concentrated among high risk populations, including IDU and FSW. The response of the government has focused on the recognized high risk populations, mainly young male drug users. This concentration on one high risk population may leave other populations under-protected or unprepared for the risk and the consequences of HIV infection. In particular, attention to women's risks of exposure and needs for care may not receive sufficient attention as long as the percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 11 publications
2
45
0
Order By: Relevance
“…Although the HIV epidemic in Viet Nam is still in a concentrated stage, the potential for a generalized epidemic is increasing, as indicated by a very high prevalence of HIV infection among high-risk groups and by a hidden epidemic among females. [5][6][7][8] Moreover, resources for HIV services mainly involve funding from international donors, which is rapidly decreasing as Viet Nam emerges as a middle-income country. According to projections of the Vietnamese National HIV Strategic Plan for 2011-2015, over this period the total cost of HIV services will increase by 60%, to approximately US$ 150 million.…”
Section: Introductionmentioning
confidence: 99%
“…Although the HIV epidemic in Viet Nam is still in a concentrated stage, the potential for a generalized epidemic is increasing, as indicated by a very high prevalence of HIV infection among high-risk groups and by a hidden epidemic among females. [5][6][7][8] Moreover, resources for HIV services mainly involve funding from international donors, which is rapidly decreasing as Viet Nam emerges as a middle-income country. According to projections of the Vietnamese National HIV Strategic Plan for 2011-2015, over this period the total cost of HIV services will increase by 60%, to approximately US$ 150 million.…”
Section: Introductionmentioning
confidence: 99%
“…21 Little is known about access to sexual and reproductive health services among people living with HIV, 22 and there is evidence that women who are not drug users or sex workers are not accessing HIV prevention, care and treatment. 23 A recent study in Hai Phong found that pregnant women do not get tested for HIV in the course of antenatal care, 24 suggesting that some women living with HIV (WLHIV) may lack the knowledge of and access to treatment and prevention of mother-to-child transmission services.…”
mentioning
confidence: 99%
“…The importance of sustained prevention efforts in Asia was confirmed by a recent meta-analysis of available data in Viet Nam, which found that many low-risk women may be at considerable risk of HIV infection due to the high-risk sexual and drug-using behaviours of their male partners (Nguyen et al, 2008). (Lu et al, 2008).…”
Section: An Evolving Epidemicmentioning
confidence: 79%